Positivity Ratio and Well-Being Among Teachers. The Mediating Role of Work Engagement - Rusu, Petruta P.; Colomeischi, Aurora A. (Frontiers in Psychology, 2020)
Previous studies indicated that the balance of positive to negative affect (i.e. positivity ratio) is associated with subjective well-being and flourishing in the general population. Moreover, a positivity ratio of 2.9 is considered a critical value discriminating between flourishing and non-flourishing individuals. To date, however, there is limited research on the positivity ratio on samples of teachers. The present study aimed to investigate whether the positivity ratio affects work engagement and well-being among teachers. Based on the Broaden-and-Build Theory (Fredrickson, 2001) and Work Engagement Model (Bakker and Demerouti, 2007) we predicted that positivity ratio (the ratio between positive and negative emotions) experienced by teachers would increase their work engagement, which in turn would positively affect their well-being. A sample of 1335 teachers (762 women and 573 men) from Romania participated in the study. Results revealed that work engagement mediated the relationship between positivity ratio and well-being. Specifically, teachers with a higher ratio of positive to negative emotions reported more engagement (dedication, absorption, and vigor) and in consequence higher levels of subjective well-being (autonomy, environmental mastery, personal growth, self-acceptance, positive relations with others and purpose in life). Also, when investigating the positivity ratio according to participants' well-being, we found a mean of positivity ratio of 2.84 for the group of teachers with high levels of well-being, validating the proposed critical positivity ratio of 2.9. These findings support the importance of addressing positive emotions and positivity ratio in prevention and intervention programs with teachers.